Mobile app for used item giveaway - Lee, Jia Yi (Nanyang Technological University, 2022)
One man's trash is another man’s treasure. Instead of throwing away unwanted items, blessing them away to others who want or need them would be bringing new life into an object that would otherwise land up in the landfill. This is especially important when trying to achieve a sustainable future for the Earth. The main objective of this project is to design and develop a mobile application for giveaway, in order to drive Singapore towards her goal of becoming a sustainable city. Users will be able to give items that they do not need, and request for items they want through the application. The application was developed using Flutter, and backend was handled using Google Firebase.